Inskrypcje w kościele pw. Zmartwychwstania Pańskiego w Bydgoszczy (Kronika Bydgoska, 2014)
Inscriptions, which are written notices on solid material, were of interest of researchers, also in Bydgoszcz. They are fruits of labor of a group of history students from the Kazimierz Wielki University in Bydgoszcz within their epigraphy lessons. The purpose of the project was recording and description of epigraphic objects located in the Parish of the Resurrection of Our Lord in Bydgoszcz. The parish complex consists of the church, rectory and belfry. The existing inscriptions can be divided into several groups: tablets, bells and stained glass windows. The most diverse group is tablets, made usually with the use of concave forging technique. All capitals was the most popular type of inscriptions. The parish has three bells made in a well-known and highly regarded bell foundry of the Felczyński family of Przemyśl in 1989. All three bells have the same pattern of ornaments. a group of small stained glass inscriptions is seen inside the church. The vast majority of inscriptions are made in the Polish language. The main part is the catalog consisting of 19 inscriptions.